A study of the psychological impact of the first point in judo competition - Huang, K.-E.; Shih, S.-C.; Liao, W.-S. (Research Journal of Budo, 2015)
The first point scored in a sporting competition is an important index which may affect the final result. In this study, we analyzed many judo matches to determine the impact of the first point scored. This can be seen as an indicator of the psychological arousal level of athletes. To evaluate this effect, we processed collected data according to the referee rules used in matches in different years. In 2008, the International Judo Federation (IJF) changed competition rules, and removed the minimum point of koka and consequently the equivalent point which is awarded resulting from the first shido. We collected competition data from actual judo matches and categorized it according to the rules used in that competition in order to be able to ascertain if the first point lost affected the psychological state of the athletes and consequently their final result. The data was tested statistically, and the results of this study show that the first point lost does have a significant impact on the results.